(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the Vitamin D3 Level in Children with Respiratory Tract Infection. Study Design: A Case Control Study Place and Duration of Study: This study was conducted at the Hospital and Research Center, Department of Pediatric, Baqai Medical University, Karachi from 6 May 2018 to 5 May 2020. Materials and Methods: The present study, conducted within a hospital setting, comprised a cohort of 128 pediatric individuals, ranging in age from six months to 15 years. These participants were selected as cases and were admitted to the hospital or attended outpatient clinics due to the presence of recurrent respiratory infections. A cohort of 42 pediatric patients, all in a state of optimal health, belonging to the same age bracket, were selected as control subjects for this study. These individuals were attending the hospital for the purpose of receiving vaccinations and undergoing routine check-ups, within the designated study period. Venous blood specimens were procured from both cases and controls in order to investigate the levels of serum 25-hydroxyvitamin D. Results: In this study, we compared the levels of 25-hydroxyvitamin D (25(OH)D) between healthy children (controls) undergoing normal checkups and children with recurrent respiratory infections (cases). This finding implies that a lack of vitamin D may increase a person's susceptibility to upper respiratory infections during particular seasons of the year. This data raises the possibility that vitamin D deficiency may be a significant factor in higher incidence of recurrent infectious rhinitis in children, children’s vulnerability to lower airway infections and recurrent otitis media and recurrent pharyngitis or tonsillitis. Conclusion: The observed study population exhibited a markedly elevated incidence of vitamin D deficiency in children presenting with recurrent respiratory infections, in stark contrast to the control group. The incorporation of vitamin D status evaluation is imperative within the comprehensive care regimen for pediatric patients exhibiting recurrent respiratory infections.